Hydropower generation from running water in irrigation and drainage canal - Veerapan, Delsyini (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
In this study, hydropower generation from running water in irrigation system was studied by using different parameters such as selection of canals, determination of the flow conditions of the canals, collection of rainfall data, determination of different head within the canal and the selection of low head turbine. This study was done because hydropower that can be produced from irrigation canal is being wasted in Malaysia. Thus, secondary and tertiary canals were selected to study the feasibilities in harnessing hydropower. The average annual rainfall was measured as 138.13mm. Rainfall collected was used to irrigate the area since it was rainy season.